Laboratory investigations following an unexpectedly positive crossmatch result in a patient awaiting renal transplantation. Issue 8 (1st August 2002) - Cole, J; Wortley, A; Stoves, J; Clark, B
Abstract : In the preparation of patients for renal transplantation tests of human leucocyte antigen (HLA) sensitisation are performed to detect "unacceptable" HLA antigens that, if present on donor cells, would be expected to result in a positive crossmatch. Individuals bearing such specificities may then be excluded from consideration as donors. Unexpected positive crossmatch results are sometimes obtained when a serum specificity has not been detected on screening. Failure to identify a donor relevant HLA antibody in a recipient at the time of crossmatch may result in hyperacute rejection of the graft. This report describes laboratory investigations performed after a positive crossmatch result in a live donor situation. The pattern of crossmatch results indicated that reactivity resulted from HLA class I antibody. Previously performed serum screening using a standard complement dependent cytotoxicity technique had failed to identify donor relevant antibody specificities in the recipient. Retrospective flow cytometric screening of the same serum samples identified an HLA-A24 specificity of donor relevance. The lower sensitivity of methods used for routine serum screening compared with those used for crossmatching accounts for the findings in this case. The laboratory has amended its serum screening protocol to include flow cytometric analysis.